Analisis Dampak Replanting Kebun Kelapa Sawit Terhadap Ekonomi Keluarga Di Kecamatan Koto Besar Kabupaten Dharmasraya - Isma Elisa; Yulhendri Yulhendri (Jurnal Salingka Nagari, 2023)
This study aims to determine the impact of replanting oil palm plantations on families in Koto Besar District, Dharmasraya Regency. This type of research is phenomenological research with a qualitative research approach. Research informants were determined using purposive sample analysis. Data collection techniques by observation and interviews. The results of this study indicate that the economic impact on farming families in Koto Besar District, Dharmasraya Regency is caused by replanting, that is, farmers cannot utilize their oil palm land as their main source of livelihood, causing a decrease in income for farmers. Farmers' efforts to replace lost income during the replanting period have other land or gardens that are managed and can produce to replace lost income during the replanting period, then too, farmers are also looking for other side jobs to add to the decrease in income during the replanting period. Based on research, the advice to farmers is that farmers must prepare themselves from the start to face the replanting period to minimize the impact on the farmers' family economy.